Determinants of Career Aspiration An Empirical Study on Masters of Business Administration Students of Selected Two National Universities in Sri Lanka - Fernando, R.T.W.; Jayasekara, P. (My University, 2015)
Area of the Study Career aspiration is one of the constructs of Career Development. Therefore this study is to identify the determinants of career aspiration and its relationship with career aspiration of Masters of Business administration (MBA) students in selected two national universities in Sri Lanka. Problem of the Study Empirical and theoretical gap to identify the determinants of career aspiration and their relationship with career aspiration of Masters of Business Administration (MBA) students in selected two national universities in Sri Lanka. Method of the Study The data was collected from 153 respondents (MBA students) in the University of Sri Jayewardenepura and University of Colombo by administrating a structured questionnaire which consisted of 22 questions/statements with five point Likert scale. The data analysis included the correlation and regression analysis conducted using SPSS 16.0 (Version). Findings of the Study It was found that there is a strong positive relationship between intrinsic factors and career aspiration. There was a moderate relationship between job related factors and career aspiration while there was a negative relationship between familial factors and career aspiration. Conclusion of the Study Since there is a strong relationship between intrinsic factors and career aspiration, when developing new career development programmes, management should pay their attention to develop individual factors.
Keywords: Career Aspiration; Intrinsic Factors; Extrinsic Factors; Job Related Factors; Familial Factors